Accountability, Transparency, and Reputation as Determinants of Zakat Paying Interest among the Millennial Generation: Empirical Evidence with Moderation of Zakat Digitalization - Siti Saritah; Dahlifah Dahlifah (Journal of Accounting, Management, and Economics Research (JAMER), 2027)
This study examines the effects of accountability, transparency, and reputation of zakat collection institutions (LAZ) on millennials’ intention to pay zakat, with zakat digitalization as a moderating variable in Greater Jakarta (Jakarta, Bogor, Depok, Tangerang, and Bekasi). Using a quantitative approach, data were collected from 400 Muslim millennials aged 29–44 who reside in Greater Jakarta and have made digital zakat payments. Respondents were selected through purposive sampling, and data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The results show that accountability and transparency significantly influence the intention to pay zakat, as millennials value responsible management and accessible information in building trust. In contrast, institutional reputation has no significant effect, suggesting that operational performance is more influential than institutional image. Digitalization moderates the effects of accountability and transparency by enabling real-time information access and verification, thereby strengthening trust and behavioral intentions. However, digitalization does not moderate the relationship between reputation and zakat payment intention. These findings highlight the importance of strengthening accountability and transparency through digital integration to optimize zakat collection among millennials.